2020
DOI: 10.1111/jcmm.16051
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐503 suppresses fibroblast activation and myofibroblast differentiation by targeting VEGFA and FGFR1 in silica‐induced pulmonary fibrosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This is consistent with the role of FGFR1 in the stimulation of angiogenesis by mediating the proliferation of both endothelial and vascular smooth muscle cells [ 24 , 25 ]. The increased FGFR1 expression in the connective tissue cells has been previously explained by its upregulation mediated by TGF-β signaling, which leads to myofibroblast differentiation and increased extracellular matrix synthesis [ 45 , 46 ]. Myofibroblasts and TGF-β signaling seem to have a central role in the pathogenesis of DD [ 37 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the role of FGFR1 in the stimulation of angiogenesis by mediating the proliferation of both endothelial and vascular smooth muscle cells [ 24 , 25 ]. The increased FGFR1 expression in the connective tissue cells has been previously explained by its upregulation mediated by TGF-β signaling, which leads to myofibroblast differentiation and increased extracellular matrix synthesis [ 45 , 46 ]. Myofibroblasts and TGF-β signaling seem to have a central role in the pathogenesis of DD [ 37 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that miR-503 modulates myofibroblast transdifferentiation and fibrosis. Wu et al [ 26 ] demonstrated that miR-503 expression was decreased in TGF-β1 stimulated lung fibroblasts and upregulation of miR-503 attenuated CAF-like myofibroblastic phenotype in myofibroblasts. Several miRNAs are involved in cardiac fibrosis (reviewed in [ 27 ]), and another study has proposed that miR-503 modulates fibrosis by enhancing the ECM deposition in cardiac fibroblasts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We can make informed assumptions and infer the involvement of specific cell types which do play an active role in tissue-specific co-expression networks ( 124 ). ATM is mainly found in endothelial and epithelial cells ( 125 , 126 ), FGFR1 in fibroblasts and epithelial cells ( 57 , 58 ), FBXW7 in hepatic stellate mesenchymal, mononuclear and pulmonary epithelial stem cells ( 60 62 ), ESR1 in myofibroblasts and epithelial cells ( 63 , 64 ), CCND1 in renal glomerular mesangial and hepatic stellate cells ( 66 , 127 ), HIF1A in renal epithelial cells and cardiac fibroblasts ( 68 , 128 ), CEBPB in hematopoietic and renal epithelial cells ( 70 , 71 ), NAMPT in hepatic stellate and renal glomerular mesangial cells ( 72 , 129 ), IRF1 in renal epithelial cells ( 76 ), SOCS1 in hepatocytes and macrophages ( 78 ), SOCS3 in cardiac fibroblasts ( 90 ), ICAM1 in endothelial cells ( 79 ), ETS1 in hepatic stellate and renal epithelial cells ( 130 , 131 ), IL7R in hepatic stellate cells ( 82 ), MMP1 in fibroblasts ( 83 , 132 ), HNF4A in hepatocytes ( 85 ), CCL2 in fibroblasts ( 86 , 133 ), CASP1 in hepatic endothelial cells ( 87 ) and STAT1 in macrophages ( 88 , 89 ). HSP90B1 , although it has been recently reported to be implicated in fibrosis ( 92 ), the specific cell type expressing it, still, remains undetermined.…”
Section: Discussionmentioning
confidence: 99%